Meningkatkan Kinerja Keuangan UMKM Melalui Literasi Keuangan, Teknologi Keuangan, dan Pengelolaan Keuangan: Studi Kasus di Kabupaten Gresik (Jurnal Kendali Akuntansi, 2025)
This study aims to analyze the influence of financial literacy, financial technology, and financial management on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Gresik Regency. The background of this study is based on the importance of strengthening the financial aspects of MSMEs as a foundation in facing the challenges of competition and economic uncertainty. The method used is a quantitative approach by distributing structured questionnaires to 96 MSMEs selected through a purposive sampling technique. The collected data were then analyzed using SPSS version 26 software to examine the relationships and influences between variables. The results show that financial literacy has a positive and significant influence on the financial performance of MSMEs. This means that the higher the level of understanding of MSMEs regarding financial management, the better the financial performance achieved. Similarly, the use of financial technology has also been shown to have a significant positive effect. The use of digital financial services such as mobile banking, e-wallets, and digital bookkeeping applications can help MSMEs simplify transactions, financial recording, and access to financing, which ultimately improves efficiency and business results. Meanwhile, the financial management variable shows a moderate influence on financial performance. This indicates that financial planning, recording, and control practices in some MSMEs are still suboptimal and need to be improved to contribute more significantly to business performance. Overall, these findings underscore the importance of improving financial literacy and adopting financial technology as key strategies for strengthening MSME performance. This research provides practical recommendations for MSMEs and stakeholders to enhance their financial management capacity to encourage sustainable business growth in the digital era.